Soliton Solutions of the Klein-Gordon-Zakharov Equation with Power Law Nonlinearity. (3rd December 2013) - Ekici, Mehmet; Duran, Durgun; Sonmezoglu, Abdullah
Abstract : We introduce a new version of the trial equation method for solving nonintegrable partial differential equations in mathematical physics. Some exact solutions including soliton solutions and rational and elliptic function solutions to the Klein-Gordon-Zakharov equation with power law nonlinearity in (1 + 2) dimensions are obtained by this method.